LEGAL PROTECTION AGAINST WOMEN VICTIMS BY THE INDONESIAN DOMESTIC VIOLENCE ACT 23, 2004 - Hanafi Arief (Sriwijaya Law Review, 2017)
Domestic Violence, particularly against women is a social phenomenon which tends to increase from year to year and even from day to day. Many countries enacted special legislation to protect women from domestic violence based on the United Nation Declaration on the Elimination of Violence Against Women (CEDAW). Indonesia adopted the conventions based on the Indonesian Act No. 7 of 1984 on the Convention on the Elimination of All Forms of Discrimination against Women, and issued Presidential Decree No. 9 of 1998 concerning the Commission on Violence against Women. Indonesia then enacted special legislation on domestic violence in 2004, namely Domestic Violence Act 23, 2004. This paper aims to understand how the Domestic Violence Act 23, 2004 protects women victims of domestic violence. The sources of law study are the basic rules and regulations, international conventions which have binding force legally. This is a library research using normative judicial approach, and the analysis is descriptive qualitative. The legal protection of women victims of domestic violence is an obligation, especially for countries that uphold human rights, because of the domestic violence constitutes crimes against humanity that are outstanding. This crime happens at any time either known or not, so it is described as an iceberg phenomenon. In addition, because this matter is private, many people do not want to intervene the matter. The strong culture of not interfering ones’ affairs also influences the police in law enforcement. Police often gives less respect for the report of the victims, and even ask the victims to go back to her husband or family